- A Novel Prognostic Signature Combining Serum Inflammatory Cytokines and Cell-Free Telomere Length in Small Cell Lung Cancer: serum levels of IL-6, IL-8, TNF-α, CRP, and cell-free telomere length (cfTL) - Pan, Mark; Fu, JingYun; Chen, Tao (Journal of Medical Biochemistry, 2026)
Background: Small Cell Lung Cancer (SCLC) remains a lethal malignancy with limited prognostic biomarkers. While systemic inflammation contributes to SCLC progression, the integration of cellular senescence biomarkers with inflammatory markers has not been explored. We hypothesized that combining serum inflammatory cytokines with cell-free telomere length would create a superior prognostic tool. Methods: In this prospective cohort study, 187 extensive-stage SCLC patients were enrolled before first-line chemo-immunotherapy. Baseline serum levels of IL-6, IL-8, TNF-α, CRP, and cell-free telomere length (cfTL) were measured. An Inflamm-Aging Index (IAI) was developed using Cox regression. Primary outcome was overall survival (OS). Results: High IL-6 (HR 2.14, 95% CI 1.45-3.16, p<0.001) and short cfTL (HR 2.87, 95% CI 1.92-4.29, p<0.001) independently predicted worse OS. The composite IAI stratified patients into low, intermediate, and high-risk groups with median OS of 14.2, 9.1, and 5.3 months, respectively (p<0.0001). The IAI remained independently prognostic after multivariable adjustment (HR 3.42, 95% CI 2.18-5.37, p<0.001). The IAI demonstrated superior discriminative ability (C-index 0.78) compared to individual biomarkers. Conclusion: The Inflamm-Aging Index, integrating inflammatory cytokines with cellular senescence biomarkers, provides a novel, non-invasive prognostic tool that significantly improves risk stratification in SCLC, potentially guiding personalized therapeutic approaches.